Reap the Benefits of a Fire Hydrant Maintenance Program. Issue 6 (30th May 2019) - Jackson, Andrew; Morgan, Kenneth C.; Notch, Steve
Abstract : Water utilities excel when they place value on and maintain each system asset in a manner that reflects its value. An effective fire hydrant maintenance program offers a wide range of system benefits.